The Effectiveness of a Home-Based Diabetes Management Program on Diabetes Control - Gülnaz Karatay; Yeliz Akkuş; Barış Öztürk; Barlas Sülü (Archives of Preventive Medicine - Peertechz Publications, 2016)
Background: Diabetes is a lifelong disease and reduces the victim's lifespan and quality of life. Diabetes management is a continuing life-long endeavor requiring cognitive, attitudinal and behavioral changes. The purpose of the study: To evaluate the effectiveness of home based diabetes management programme on diabetes control conducted by health team. Methods: This study which was designed as a one-group pretest-posttest pattern. Home visits were carried out once a week for nine weeks for 52 patients. The obtained data were evaluated by using percentages, t-test and the McNemar signifi cance test. Results: At the completion of the intervention, life-style changes, such as the frequency of controlling blood glucose, glycemic control, exercise, and increasing vegetable and fruit consumption all produced changes which proved statistically significant and positive. Similarly, in comparison to before the intervention, the results after completion of the intervention showed that the values of patients' weight (86.28 ± 13.50, 80.40 ± 23:13), systolic blood pressure (139.75 ± 17.53, 135.31 ± 17.91), and postprandial blood glucose (265.63 ± 128.63, 215.48 ± 69.71) had all statistically and significantly decreased (p <0.05).